APLIKASI HUMAN RESOURCE DEVELOPMENT DENGAN FITUR PEREKRUTAN MENGGUNAKAN METODE NAIVE BAYES BERBASIS WEB - Wimvy Nanda Tanius; Bagus Mulyawan; Janson Hendryli (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Human Resource Development (HRD) is required as a forum for development of all Human Resources (HR) in the company. The task of HRD itself is to conduct attendance per employee, number of employees, accept and reject employees, and perform tasks from interviews for the company itself. Every company must have a division of HRD. Each company is engaged in different fields. Companies are required to recruit employees by HRD departments. The process of selecting prospective employees in a position that is done manually by reading the background of each prospective employee. Therefore, an application for HRD in which the application can determine the right position for prospective employees. Thus it can simplify and accelerate the work of HRD in determining the right job for prospective employees. In the process of placement of this position using the Naïve Bayes method. This app can put everyone in their job positions based on the personality descriptions and skills of each prospective worker.